Growth trajectory analysis of Pacific whiteleg shrimp (Litopenaeus vannamei): Comparison of the specific growth rate, the thermal‐unit growth coefficient and its adaptations. (13th November 2019) - Powell, Christopher D.; Tansil, Fiona; France, James; Bureau, Dominique P.
Abstract: Empirical growth models have widespread application in the field of aquaculture. These models allow estimates of harvest size and waste outputs in addition to nutrient and feed requirements. In an effort to increase the ability to predict shrimp growth, the specific growth rate (SGR) and thermal‐unit growth coefficient (TGC) models were fitted to 15 datasets encompassing growth of Pacific whiteleg shrimp ( Litopenaeus vannamei ). Shrimp were reared under commercial conditions in Southeast Asia with weights ranging from 0.01 g to 34 g. Growth rates were regressed against body weights to identify changes in growth pattern across life stages. Analysis identified two distinct patterns of growth, with a break point between stanzas at 7.5 g. The body weight exponent of the TGC model, traditionally assumed to be (1 − b ) = 1/3, was solved for iteratively in each identified growth stanza in an effort to improve the goodness of fit of the TGC model. Average body weight exponents in the first and second stanzas were 0.416 and 0.952 respectively. Projected growth trajectories using these exponents resulted in significantly better fits in comparison to the traditional TGC and the SGR on the basis of statistical measures of goodness of fit.